1969
DOI: 10.1161/01.res.24.3.361
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Transmembrane Potentials in Canine Purkinje Fibers and at Purkinje Fiber-Muscle Junctions

Abstract: Interactions between Purkinje fibers and ventricular muscle were studied in canine Purkinje-papillary muscle preparations. The change in duration of action potentials across the junctions between Purkinje fibers and papillary muscle was continuously graded, not abrupt. The transmembrane action potentials were longest in the false tendons and progressively shorter in more peripheral fibers. The responses of terminal Purkinje fibers and of neighboring muscle cells differed little in duration. The shortest action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(73 citation statements)
references
References 9 publications
7
66
0
Order By: Relevance
“…20 In experimental models of myocardial ischemia, demonstration of the association of QRS prolongation with Purkinje-ventricular conduction delay is further support for this mechanism. [24][25][26] Consistently, the correlation we detected between admission QRS duration and ischemia duration in our study group is in favour of the idea of ischemia as a mechanism of QRS prolongation. QRS prolongation might be a sign of extensive ischemia and a poor metabolic state, which was shown to worsen with the delay in reperfusion.…”
Section: Interpretation Of Ecg Findingssupporting
confidence: 84%
“…20 In experimental models of myocardial ischemia, demonstration of the association of QRS prolongation with Purkinje-ventricular conduction delay is further support for this mechanism. [24][25][26] Consistently, the correlation we detected between admission QRS duration and ischemia duration in our study group is in favour of the idea of ischemia as a mechanism of QRS prolongation. QRS prolongation might be a sign of extensive ischemia and a poor metabolic state, which was shown to worsen with the delay in reperfusion.…”
Section: Interpretation Of Ecg Findingssupporting
confidence: 84%
“…Prolongation of QRS that occurs during acute coronary obstruction is mostly due to slowing of conduction within the ischemic areas and this mechanism was proved in several experimental models and human studies [17][18][19][20]. In our study, we analyzed QRS complex duration changes on admission, at 60 and 90 min post reperfusion and we found that there is no significant difference between the two groups regarding the admission QRS but there is a significant prolongation of the QRS duration in 60 min and 90 min post reperfusion ECG in the group with impaired perfusion compared to group with a successful perfusion and our findings are in agreement with several published studies.…”
Section: Discussionmentioning
confidence: 94%
“…We found that this intervention has approximately equal effects on the two sequential steps involved in P-VM conduction. We then analyzed the increased delay from T cells and V cells on the basis of three hypothetical mechanisms: 1) increased coupling resistance, 2) decreased V cell excitability, and 3) decreased cellular responsiveness of the T cells. Our results show that the effects of elevated [K+J0 and hypoxia on T-VM delay can be accounted for by a decreased responsiveness of the T cells without any significant electrical uncoupling between T and V cells or decrease in VM excitability.…”
mentioning
confidence: 99%